Povezanost med rakom in onesnaževali, ki nastanejo v procesih sežiga in sosežiga odpadkov: krovni pregled literature - Oblak, Teja (Onkologija (Ljubljana), 2023)
Introduction: During the process of waste incineration, co-incineration and cement production, various emissions are released into the environment containing different pollutants. The aim was to assess a possible association between exposure to pollutants emitted from co-/incinerators and cement plants and cancer in occupationally exposed persons and residents living near these plants. Methods: Inclusion criteria for the umbrella review were meta-analyses and systematic literature reviews, English, period 1980– 2023. Searches were performed in 4 databases (PubMed, Scopus, Web of Science, Cochrane Reviews). The quality of documents was assessed by AMSTAR-2 (methodology) and GRADE (evidence) tools. Results: Of 7 701 documents, 14 were finally included (5 meta- -analyses, 9 systematic reviews). There is some low to moderate evidence of an association between soft tissue sarcomas and non-Hodgkin lymphomas in population exposed to dioxins near I generation incinerators, but there is no evidence for next generation incinerators. To date, there is no evidence for co-incinerators. There is moderate evidence for an association between incidence of all cancers, lung, prostate, stomach and oropharyngeal cancer and exposure to chromium in occupationally exposed persons at I.-II. generation cement plants. Most of the evidence is limited due to mixed results, differences in question´ technique, heterogeneity, and potential bias. Conclusions: There is limited evidence for an association between cancer and exposure to pollutants emitted from I. generation incinerators and I.-II. generation cement plants. To evaluate the possible association between pollutant emissions from the most modern co-incinerators, it seems reasonable to plan targeted epidemiological studies and human biomonitoring studies.
Keywords: cementarna; odpadki; onesnaževala; rak; sežig; sosežig